2014
DOI: 10.1002/csr.1355
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility in the Process of Attracting College Graduates

Abstract: Corporate social responsibility (CSR) is acquiring great relevance in academic and professional fields as a tool which enables an increase in business competitiveness and sustainable development. Additionally, a growing number of authors have started to consider CSR as an internal capability that allows firms to attract and retain a qualified workforce. Taking into account this premise, this study has a two‐fold aim: (i) to analyse which CSR aspects are assessed higher or lower by valuable human capital such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…In turn, Sobczak et al [56] found that the students' perception of CSR is dependent not only on the content of the program, but also on the integration of CSR into the culture of these higher education institutions. This is supported by Barrena-Martinez et al [57] who concluded that social integration factors have a greater impact on the perception of CSR than explanatory factors. The CSR-sensitive mindset of students can be trained in cases in which the curriculum integrates care theory with CSR teaching [58].…”
Section: Literature Reviewmentioning
confidence: 61%
See 1 more Smart Citation
“…In turn, Sobczak et al [56] found that the students' perception of CSR is dependent not only on the content of the program, but also on the integration of CSR into the culture of these higher education institutions. This is supported by Barrena-Martinez et al [57] who concluded that social integration factors have a greater impact on the perception of CSR than explanatory factors. The CSR-sensitive mindset of students can be trained in cases in which the curriculum integrates care theory with CSR teaching [58].…”
Section: Literature Reviewmentioning
confidence: 61%
“…While researchers from Western countries sometimes show the ongoing withdrawal of enterprises from the very idea of CSR and present themselves to stakeholders by imitating CSR as one of the marketing tools [3][4][5][6], or even lobbying [7] (pp. [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], it is becoming a clear trend in post-Soviet countries. Therefore, attention is paid to the fact that the implementation of CSR should be oriented not towards charity, marketing, and public relations, but should first and foremost be understood as social responsibility towards stakeholders [8].…”
Section: Introductionmentioning
confidence: 99%
“…Research on job seekers' attraction to CSR concentrates on analyses regarding personal factors, such as gender, age, and knowledge of CSR (Arlow, ; Albinger & Freeman, ; Eweje & Brunton, ; Evans & Davis, ; Fitzpatrick, ; Barrena‐Martínez et al , ; Tormo‐Carbó et al, ). Barrena‐Martínez et al () conclude, however, that social integration factors – such as collaboration with non‐governmental organizations (NGOs) and prior awareness of CSR – have a higher influence on the positive assessment of CSR and hence on the attraction and retention of college graduates than personal factors. Therefore, we assume that it is not only the specific content of CSR communication that may influence job seekers' responses, but rather their individual attitudes toward CSR itself.…”
Section: Csr Understanding and Employer Attractivenessmentioning
confidence: 99%
“…Concepts such as sustainability, corporate social responsibility (CSR), corporate governance, and business ethics have been a reference point in both business and education for some time now (Matten & Moon, ; Barrena‐Martínez et al, ). Largely, society has become aware of the fact that the current economic development model is not sustainable and that education and training are essential to the sustainability of our system (Kim et al, ; Jim & Shen, ) and therefore the consideration of sustainability in educational curricula is no longer an option but a priority.…”
Section: Introductionmentioning
confidence: 99%
“…From this premise, the assumption is that the driving objective for any organization, traditionally, is to maximize profits. For some time now, however, we have witnessed the advance of another set of values and priorities in society (Doh & Tashman, 2014;Barrena-Martínez et al, 2015). Companies must continue to generate profit; yet they are increasingly expected to pay attention to other details such as the quality of their relationships with stakeholders or dealing with social and environmental concerns (Russo & Perrini, 2010;Boesso et al, 2015;Martín de Castro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%